2007
DOI: 10.1111/j.1442-2042.2006.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Head‐to‐head comparison of retropubic, perineal and laparoscopic radical prostatectomy

Abstract: Objective: As more patients are diagnosed with prostate cancer at an early stage, it is becoming increasingly important to refine the technique of surgical excision. For this purpose we have generated objective data comparing three different surgical approaches used by three experienced surgeons. Methods: We prospectively compared three contemporary personal series of 50 consecutive radical prostatectomy (RP) patients. The healthrelated quality of life was evaluated preoperatively and in months 1, 3, 6, 12 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
0
23
1
6
Order By: Relevance
“…17 Various studies have reported erectile function outcomes after radical prostatectomy, 18 brachytherapy, 19 or external-beam radiotherapy with or without brachytherapy 20,21 using the IIEF-5. Many more studies have used the EPIC to assess ED in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 Various studies have reported erectile function outcomes after radical prostatectomy, 18 brachytherapy, 19 or external-beam radiotherapy with or without brachytherapy 20,21 using the IIEF-5. Many more studies have used the EPIC to assess ED in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…61 Similarly, the total volume of cancer identified by pathological examination of the whole prostate after radical prostatectomy has been assessed as a possible predictive factor for recurrence but was found not to be independently significant on multivariate analysis. 62 These pathological measures of cancer extent have not been included in our care pathway given the current uncertainty of the evidence base.…”
Section: Cancer Extentmentioning
confidence: 99%
“…All studies reported age with a median (interquartile range) of 62 (60)(61)(62)(63)(64) years and a total range of 35-84 years.…”
Section: Characteristics Of Patientsmentioning
confidence: 99%
“…В мире накоплен большой опыт выполнения РППЭ больным РПЖ. Благодаря на-копившемуся опыту хирургов частота осложнений после РППЭ в последние годы значительно снизилась [3][4][5].…”
unclassified
“…N. Schmeller и соавт. [5] сравнили результаты позадилонной, промежностной и лапароскопической РПЭ. Среднее время операции соста-вило 147, 110 и 240 мин соответственно.…”
unclassified